Association Between MicroRNAs Polymorphisms and Risk of Ischemic Stroke: A Meta-Analysis in Chinese Individuals - Li, Chen-Xi; Weng, Hong; Zheng, Jun; Feng, Zhi-He; Ou, Jian-Lin; Liao, Wei-Jing (Frontiers in Aging Neuroscience, 2018)
Objective: Previous studies have demonstrated that some single-nucleotide polymorphisms (SNPs) in miRNAs are related to the risk of ischemic stroke (IS), but the conclusions are still controversial and inconclusive. We performed this meta-analysis to further assess the association between miR-146a C>G (rs2910164), miR-149 T>C (rs2292832), miR-196a2 T>C (rs11614913), miR-499 A>G (rs3746444) and risk of IS in Chinese individuals. Methods: Relevant studies were identified in the databases of PubMed, Embase. The strength of correlation between microRNAs polymorphisms and IS risk was assessed by odds ratios (ORs) and 95% confidence intervals (95% CIs) under five genetic models. Results: 5 studies, containing 2632 cases and 3191 controls, were included in this meta-analysis. The overall results of meta-analysis indicated that there were no significant association between miR-146a C>G (rs2910164), miR-149 T>C (rs2292832), miR-196a2 T>C (rs11614913) and the IS risk in the overall analyses. MiR-499 A>G (rs3746444) was associated with an increased IS risk under allele model (OR=1.36, 95% CI=1.20-1.83), heterozygous model (OR=1.35, 95% CI=1.01-1.79) and dominant model (OR=1.30, 95% CI=1.02-1.80) in Chinese. The sensitivity analysis results of these four polymorphisms were similar to the overall results. Conclusion: MiR-499 A>G (rs3746444) G allele and AG, AG+AA genotype might be risk factors of IS in Chinese. No significant association was observed between miR-146a C>G (rs2910164), miR-149 T>C (rs2292832), miR-196a2 T>C (rs11614913) and IS risk. The associations may be different due to geographical factors of China. More explorations in more diverse geographically regions with large sample size are expected to further verify the findings in the future.